2019
DOI: 10.1152/jn.00274.2019
|View full text |Cite
|
Sign up to set email alerts
|

Heterosynaptic facilitation of mechanical nociceptive input is dependent on the frequency of conditioning stimulation

Abstract: High-frequency burstlike electrical conditioning stimulation (HFS) applied to human skin induces an increase in mechanical pinprick sensitivity of the surrounding unconditioned skin (a phenomenon known as secondary hyperalgesia). The present study assessed the effect of frequency of conditioning stimulation on the development of this increased pinprick sensitivity in humans. In a first experiment, we compared the increase in pinprick sensitivity induced by HFS, using monophasic non-charge-compensated pulses an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 39 publications
1
23
1
Order By: Relevance
“…It was plausible that the individual calibration approach could have confounded the results because the current for the HFS was linked to the individual detection threshold, and HFS delivered at a higher current could result in greater secondary hyperalgesia. Although previous published datasets ( Torta et al, 2017 ; van den Broeke et al, 2017 ; van den Broeke et al, 2019 ; van den Broeke et al, 2019 ; Van den Broeke et al, 2016 ; van den Broeke, Lenoir & Mouraux, 2016 ) ( n = 170, unpublished) investigation found no association between the individual electrical detection threshold and the magnitude of secondary hyperalgesia. We checked this by testing for a correlation between the individually determined electrical detection threshold and magnitude of secondary hyperalgesia in our data.…”
Section: Methodsmentioning
confidence: 69%
“…It was plausible that the individual calibration approach could have confounded the results because the current for the HFS was linked to the individual detection threshold, and HFS delivered at a higher current could result in greater secondary hyperalgesia. Although previous published datasets ( Torta et al, 2017 ; van den Broeke et al, 2017 ; van den Broeke et al, 2019 ; van den Broeke et al, 2019 ; Van den Broeke et al, 2016 ; van den Broeke, Lenoir & Mouraux, 2016 ) ( n = 170, unpublished) investigation found no association between the individual electrical detection threshold and the magnitude of secondary hyperalgesia. We checked this by testing for a correlation between the individually determined electrical detection threshold and magnitude of secondary hyperalgesia in our data.…”
Section: Methodsmentioning
confidence: 69%
“…The total duration of their conditioning stimulation was around 16 min, and the stimulation was applied to the ventral forearm. Also Torta et al (2019) showed an increase in pinprick sensitivity of the skin after 2 min of 2-Hz continuous stimulation at the forearm.…”
Section: Discussionmentioning
confidence: 87%
“…In experiment 2, 40 healthy volunteers were included (5-Hz burst-like stimulation: n ϭ 20, 7 men and 13 women; age 18 -40 yr, 23.0 Ϯ 4.9 yr; 5-Hz continuous stimulation: n ϭ 20, 7 men and 13 women; age 19 -27 yr, 22.6 Ϯ 2.3 yr). Parts of the data were reused from the 5-Hz continuous stimulation condition of experiment 1 (n ϭ 15) and the 5-Hz burst-like stimulation condition of our previously collected data set (n ϭ 15; van den Broeke et al 2019). Comparison of these two groups of 15 participants did not reach statistical significance.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, capsaicin or heat typically induces after-sensations, which is not the case for electrical stimulation. Furthermore, parameters such as the pattern and frequency of electrical stimulation can be easily controlled, which has recently led to the finding that burst-like 42 Hz stimulation seem the optimal parameters for inducing SH (Van Den Broeke et al, 2019;Gousset et al, 2019).…”
Section: Introductionmentioning
confidence: 99%